2016
DOI: 10.3390/ijms17122075
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Mitochondrial cAMP/PKA Signaling Is Involved in Sepsis-Induced Mitochondrial and Myocardial Dysfunction

Abstract: Adrenergic receptors couple to Gs-proteins leading to transmembrane adenylyl cyclase activation and cytosolic cyclic adenosine monophosphate (cAMP) production. Cyclic AMP is also produced in the mitochondrial matrix, where it regulates respiration through protein kinase A (PKA)-dependent phosphorylation of respiratory chain complexes. We hypothesized that a blunted mitochondrial cAMP-PKA pathway would participate in sepsis-induced heart dysfunction. Adult male mice were subjected to intra-abdominal sepsis. Mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
(64 reference statements)
1
21
0
1
Order By: Relevance
“…In alignment with these results, a recent report suggested that PDE2 inhibition has a protective effect in a brain ischemia/reperfusion model, although it was delayed rather than acute effects of reperfusion that were analyzed [ 123 ]. Similarly, an inhibition of matrix localized PDE2A with BAY60-7550 reduced the uncoupled respiration rate and increased cytochrome c oxidase activity in septic mice [ 124 ].…”
Section: Functional Role Of Sac In Different Cellular Compartmentsmentioning
confidence: 99%
“…In alignment with these results, a recent report suggested that PDE2 inhibition has a protective effect in a brain ischemia/reperfusion model, although it was delayed rather than acute effects of reperfusion that were analyzed [ 123 ]. Similarly, an inhibition of matrix localized PDE2A with BAY60-7550 reduced the uncoupled respiration rate and increased cytochrome c oxidase activity in septic mice [ 124 ].…”
Section: Functional Role Of Sac In Different Cellular Compartmentsmentioning
confidence: 99%
“…The mitochondrial cAMP-PKA pathway couples the Krebs cycle and OXPHOS activity to generate ATP. In a mouse model of acute peritonitis, Neviere et al observed that sepsis-related cardiomyopathy was associated with impaired cAMP-PKA signaling, decreased complex IV phosphorylation of serine 58, decreased mitochondrial RCR, and left ventricle contractile dysfunction [ 51 ]. Ex vivo inhibition of phosphodiesterase 2A by mitochondria-permeant Bay 607550 prevented mitochondrial cAMP depletion, complex IV phosphorylation, OXPHOS uncoupling, and contractile dysfunction.…”
Section: Oxidative Phosphorylation Disorders Of Myocardial Mitochomentioning
confidence: 99%
“…Furthermore, Neviere et al, indicated that PDE2 inhibition in septic cardiac fibers was beneficial as it limited sepsis-induced myocardial dysfunction and improved mitochondrial respiration [ 194 ]. Since sAC-induced cytochrome c oxidase phosphorylation is PKA-dependent, PDE2 inhibition partially increased cytochrome c oxidase subunit IV-1 protein phosphorylation in septic cardiac fibers.…”
Section: Role Of Pde2 In Cardiovascular Diseasementioning
confidence: 99%
“…Moreover, perfusion of isolated septic hearts with the PDE2 inhibitor BAY60-7550 increased left ventricular developed force. Consistently, pretreatment with BAY60-7550, prior to a cecal ligation puncture procedure to induce sepsis, also significantly reduced coronary perfusion pressure and improved cardiac efficiency in septic mice in vivo [ 194 ]. Collectively, PDE2 inhibition improves myocardial function in septic hearts by maintaining endothelial barrier integrity and improving mitochondrial respiration.…”
Section: Role Of Pde2 In Cardiovascular Diseasementioning
confidence: 99%